THE MEDIATING ROLE OF FLEXIBLE WORK IN THE RELATIONSHIP BETWEEN ADAPTIVE LEADERSHIP AND EMPLOYEE PRODUCTIVITY - Siregar, Muhammad Arsyad; Setiani, Setiani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
In today’s dynamic and competitive work environment, adaptive leadership has emerged as a key driver for enhancing employee productivity by enabling organizations to effectively respond to rapid change. However, the effectiveness of adaptive leadership is often influenced by workplace practices, particularly those that provide autonomy and flexibility. This study investigates the mediating role of flexible work in the relationship between adaptive leadership and employee productivity in a media company in Malang, Indonesia. A quantitative research design was employed, using survey data collected from 34 employees, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that adaptive leadership significantly and positively affects employee productivity, both directly and indirectly, through flexible work arrangements. Flexible work partially mediates this relationship, indicating that adaptive leaders can enhance productivity more effectively when supported by flexible work practices. This study contributes to the literature on leadership and organizational behavior by integrating adaptive leadership theory with flexible work to predict productivity outcomes. Practical implications are offered for organizations aiming to align leadership practices with flexible work to maximize performance.